Screening of rhizobacteria from rhizosphere of healthy chili to control bacterial wilt disease and to promote growth and yield of chili - YULMIRA YANTI; FUJI FEBRIA ASTUTI; TRIMURTI HABAZAR; CHAINUR RAHMAN NASUTION (Society for Indonesian Biodiversity, 2017)
Abstract. Yanti Y, Astuti FF, Habazar T, Nasution CR. 2017. Screening of rhizobacteria from rhizosphere of healthy chili to control bacterial wilt disease and to promote growth and yield of chili. Biodiversitas 18: 1-9. Bacterial wilt on chili cause by Ralstonia solanacearum. This disease is important, causing plant death and significant yield losses. Biological control is desirable because control with other methods gives variable results. One of the important group of biological agent is the plant growth promoting rhizobacteria (PGPR). This group can control plant pathogens and enhance the growth and yield through direct and indirect mechanisms. The aim of this research was to obtain indigenous rhizobacterial isolates from rhizosphere of healthy chili, which are effective to control bacterial wilt disease and to promote plant growth as well as to increase plant yields. The rhizobacterial isolates were collected from healthy chili rhizosphere in endemic area of bacterial wilt at Banuhampu Sub-district, Agam District, West Sumatra, Indonesia. Screening method of rhizobacterial isolates to control bacterial wilt was based on in planta technique. This technique was consist of three steps, as follow: (i) Screening of 43 rhizobacterial isolates to induce the hypersensitive reaction on Mirabilis jalapa. (ii) Screening of 42 rhizobacterial isolates (from first step) to increase growth of chili seedlings and (iii) Screening of 20 selected rhizobacterial isolates (from second step) to control bacterial wilt on chili. R. solanacearum were inoculated on the 6 weeks chili plants using Two strains of rhizobacterial isolates from chili rhizosphere (RZ.2.1.AG1 and RZ.1.3.AP1) showed high potential for disease suppression and also increased growth and yield of chili.Keywords: chili, indigenous rhizobacteria, in planta technique, Ralstonia solanacearum, screeningAbbreviations: BCA = Biocontrol agent, HR = Hypersensitive reaction, IAA = Indole Acetic Acid, IRB = Indigenous Rhizobacteria, ISR = Induce systemic resistance, NA = Nutrient agar, PGPR = Plant Growth Promoting Rhizobacteria, R = Ralstonia, TZC = triphenyl tetrazolium chloride